1990
DOI: 10.1128/aem.56.12.3755-3759.1990
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Lyase Activity in a Penicillium italicum Strain

Abstract: An extracellular pectin lyase (PNL) [poly-(methoxygalacturonide)lyase; EC 4.2.2.10] produced by Penicillium italicum CECT 2294 grown on a surface bran (natural medium) or in a submerged (synthetic medium) culture was investigated. Both culture filtrates showed macerating activity at low pH on cucumber, potato, and orange tissues. The physicochemical properties of the enzyme obtained from both culture methods were identical, as well as its catalytic properties, which were assayed by different methods. The molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…Pectin lyase (PL: EC 4.2.2.2) activity was determined spectrophotometrically with a Hitachi U-2OOO spectrophotometer by monitoring the increase in the A,,, (Albersheim 1966;Alana et al 1990). The reaction mixture (1.25 ml) contained 0.1 mol I-' citratephosphate buffer (pH 6.0), 0.5% (w/v) citrus pectin (D.E.…”
Section: E N Z Y M E a S S A Ymentioning
confidence: 99%
“…Pectin lyase (PL: EC 4.2.2.2) activity was determined spectrophotometrically with a Hitachi U-2OOO spectrophotometer by monitoring the increase in the A,,, (Albersheim 1966;Alana et al 1990). The reaction mixture (1.25 ml) contained 0.1 mol I-' citratephosphate buffer (pH 6.0), 0.5% (w/v) citrus pectin (D.E.…”
Section: E N Z Y M E a S S A Ymentioning
confidence: 99%
“…The authors reported slight inhibition of PG action in the presence of Zn 2+ and Ba 2+ and that the enzyme activity was completely lost in the presence of Hg 2+ . Similarly Ca 2+ , Mg 2+ , Mn 2+ and Zn 2+ were reported to activate pectinase from Penicillin italicum, but it was inhibited by Cu 2+ and Fe 2+ [25]. Mg 2+ and Zn 2+ stimulated pectinase activity by 115 and 138% respectively as compared to native enzyme activity [26].…”
Section: Resultsmentioning
confidence: 94%
“…The effect of temperature on enzyme activity was studied by incubating 1mL of the enzyme solution contained in test tube and 1 mL of 1% citrus pectin solution prepared in 2 mL of 0.2 M potassium phosphate buffer (pH 5.6) for 2 h at various temperatures (20,25,30,35,40,45, 50, 55 and 60 °C) in a thermo static water bath (Kottermann, Bremen, Germany). The reaction was stopped by the addition of 2 mL DNS reagent and the enzyme activities were determined.…”
Section: The Effect Of Temperature On Enzyme Activitymentioning
confidence: 99%
“…Among the pectinases, pectin lyase (PL) is of particular interest because it acts directly on pectin without the need for previous action by other enzymes of the pectinolytic complex (1). Degumming of ramie fibers with PL of Penicillium griseoroseum produces fibers with quality superior to those produced by a commercial enzyme complex because P. griseoroseum does not produce cellulolytic enzymes (10).…”
Section: Introductionmentioning
confidence: 99%
“…Among the filamentous fungi, some of the genus Penicillium are good producers of PL (1). Penicillium griseoroseum produces PL when grown in a medium containing pectin (10), its natural inducer.…”
Section: Introductionmentioning
confidence: 99%